Manajemen Inovasi Pelayanan Publik Dalam Penyelengaraan E-Goverment Pada Mall Pelayanan Publik Di Kota Payakumbuh - Rizki Ananda, Bobi; Ariany, Ria (LPPM STISIP IMAM BONJOL, 2025)
This study aims to explain service innovations in the field of Administration that have been carried out through the Public Service Mall by the Payakumbuh City government so that the services provided to the public are better. So far, what has happened in the community is the existence of bad services carried out by various agencies or local government organizations. This study uses qualitative research methods with data collection techniques through interviews, observation and documentation. The informant came from the Payakumbuh City Disdukcapil. The results of this study indicate that the Payakumbuh City Civil Registry Office has succeeded in becoming the best City Civil Registry Officer in the Population Administration Implementation (Adminduk) assessment. This can be seen in 2022 Payakumbuh City Dukcapil won 1st place in public service delivery at the West Sumatra Province level.